Empowering Nasyiatul Aisyiyah Health Cadres in Assisting Pregnant Women in Preparation for Normal Delivery through a Holistic Approach - Nova Elok Mardliyana; Umi Ma'rifah; Nur Hidayatul Ainiyah; Firdausi Nuzula (Universitas Muhammadiyah Surakarta, 2025)
Reducing maternal and infant mortality rates and improving the quality of normal delivery are major challenges in health services in Indonesia. In an effort to support this, empowering health cadres is an important key to improving community knowledge and skills, especially in assisting pregnant women during pregnancy and preparing for childbirth. This community service program aims to empower Nasyiatul Aisyiyah health cadres in assisting pregnant women with a holistic approach. This approach includes physical, psychological, social, and spiritual aspects, to ensure the readiness of pregnant women in facing a safe and healthy normal delivery process. The activities carried out include cadre training, providing educational materials related to preparation for normal delivery, and assistance to pregnant women in Malang City. The results of this activity show an increase in the knowledge and skills of health cadres regarding the importance of a holistic approach in assisting pregnant women and increasing the readiness of pregnant women both physically and mentally for normal delivery. It is hoped that this activity can contribute to reducing maternal and infant mortality rates and strengthening the capacity of East Java Nasyiatul Aisyiyah health cadres in the community.